The unmet needs of palliative care among patients with non-malignant chronic illness in Indonesia: A phenomenology study - Rona Cahyantari Merduaty; Tuti Nuraini; Sihwastuti Sihwastuti (JKP (Jurnal Keperawatan Padjajaran), 2024)
Background and Objectives: People with chronic illness tend to report multiple and complex symptoms that decrease their ability to meet their needs and quality of life (QoL). As an approach to address people with chronic illness, palliative care is still shortly focused on people with chronic malignancies in Indonesia. Eventually, that paradigm makes the spectrum of palliative care interpreted narrowly only for cancer or end-of-life (EOL) patients. This study explores the experience and needs of patients diagnosed with non-malignant chronic illness towards their illness to identify the need for palliative care. This study used a qualitative method with a phenomenological approach.